The effect of halal brand awareness on purchase intention in indonesia: the mediating role of attitude - Abdul Aziz Nugraha Pratama; M. Luthfi Hamidi; Edi Cahyono (Cogent Business & Management)
This research investigated the relationships between the awareness of halal-based products and services and people’s intention to purchase. Also, it explored behavioral attitude as a mediating variable in influencing purchase intention. Data was collected through an online survey with 162 validated respondents. The PLS-SEM method was applied to test four hypotheses connecting the relationship between brand, attitude, and intention variables. The research findings showed that all hypotheses were confirmed, including the mediating role of attitude. This means that halal industry players should respond to consumers shifting from conventional to halal lifestyle orientation, while the regulator requires to provide incentives for promoting a greater halal ecosystem. The originality of this research is that this study strengthened previous research on the role of consumers’ attitudes that positively affect the intention to purchase halal products and services. This study revealed that consumers expand their consumption of traditional halal products and services (food, Islamic banking, fashion) to lifestyle (shopping) and well-being (fitness and swimming pool).